2017
DOI: 10.4274/tjps.85057
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Toxicity of Agmatine in Rats

Abstract: ÖZAmaç: Bu çalışmanın amacı sıçanlarda ilk kez tekrarlayan agmatin uygulamasının sensorimotor kapılama sistemi üzerine etkilerini incelemekti, ancak subkütan uygulamada karşımıza çıkan beklenmedik ülseratif nekrotik lezyonlar bu konuya odaklanmamıza neden oldu. Gereç ve Yöntemler: İlk grup deneylerde, erkek Wistar albino sıçanlara 14 gün süreyle subkütan yoldan agmatin (40, 80 ve 160 mg/kg) veya salin (kontrol grubu) enjeksiyonu yapıldı (n=8 her bir grup). Uygulamaların üçüncü gününden itibaren agmatin verilen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For example, cedarwood oil applied dermally to F344/N rats and B6C3F1/N mice for 13 weeks induced ulceration, irritation, and thickened skin at a concentration of 12.5% [26]. Prolonged subcutaneous administration of agmatine, a polyamine produced by arginine decarboxylation, leads to ulceration and hair loss on the dorsal skin [27]. Our cage-side observation data indicate that PEGDE, subcutaneously injected at concentrations of more than 10,000 µg, can induce epidermal ulcers and hair loss around the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cedarwood oil applied dermally to F344/N rats and B6C3F1/N mice for 13 weeks induced ulceration, irritation, and thickened skin at a concentration of 12.5% [26]. Prolonged subcutaneous administration of agmatine, a polyamine produced by arginine decarboxylation, leads to ulceration and hair loss on the dorsal skin [27]. Our cage-side observation data indicate that PEGDE, subcutaneously injected at concentrations of more than 10,000 µg, can induce epidermal ulcers and hair loss around the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamine stress has been associated with many mental disorders, primarily suicide (5). In addition to mental problems, polyamine stress has also been reported to be associated with many types of cancer (21). It has been reported that the use of agmatine as a food supplement by bodybuilders for pain relief effect can cause some negative effects due to its potential addictive effect (10).…”
Section: Discussionmentioning
confidence: 99%